Cycles, Eulerian digraphs and the Schönemann-Gauss theorem - Steinlein, Heinrich (Topological Methods in Nonlinear Analysis, 2021)
In 19th century, Fermat’s little theorem ``a^pa(mod p) for aZ, p prime’’ was generalized in two directions: Schönemann proved a corresponding congruence for the coefficients of monic polynomials, whereas Gauss found a congruence result with p replaced by any nN. Here, we shall give an elementary proof of the common generalization of these two results.